(untitled) (Research, Society and Development, 2024)
Introduction: Posterior crossbite is a common malocclusion in orthodontics. It often accompanies maxillary atresia, leading to unilateral or bilateral posterior crossbite. Rapid maxillary expansion (RME) is an approach to treat atresia, correct transverse discrepancies, and increase the perimeter of the maxillary arch. Objective: To present the case of an 8-year-old patient with maxillary atresia, skeletal Class I, dental Class I, and no space in the maxillary anterior and mandibular regions for the alignment of the incisors. Clinical procedures: RME was performed using a HYRAX type expander. After 20 days of daily activations, there was a change in the morphology of the palate, an increase in the arch perimeter, facilitating the eruption of incisors and canines. Final considerations: RME is an effective and efficient orthopedic treatment, recommended for correcting transverse deviations, normalizing structural and functional problems. As positive side effects, the indirect action on the mandibular molars and canines allowed the alignment of the incisors.